General Methodology to Identify the Minimum Alphabet Size for Heteropolymer Design. Issue 7 (7th May 2019) - Cardelli, Chiara; Nerattini, Francesca; Tubiana, Luca; Bianco, Valentino; Dellago, Christoph; Sciortino, Francesco; Coluzza, Ivan
Abstract: Understanding how to design the structure of heteropolymers through their monomer sequence will have a significant impact on the creation of novel artificial materials. According to mean‐field theories, the minimum number—or alphabet—of distinct monomers necessary to achieve such designability is directly related to the conformational entropy ω of compact polymer structures. Here, a computational strategy to calculate this conformational entropy is introduced and thus predict the minimum alphabet to achieve designability, for a generalized heteropolymer model. The comparison of the predictions with previous results proves the robustness of the approach. It is quantified for the first time how the number of directional interactions is critical for achieving the designability. The methodology that is introduced can be easily generalized to models representing specific polymers. A comparison between conventional polymers monomers are provided, and it is predicted that polyurea, polyamide, and polyurethane residues are optimal candidates to be functionalized for the experimental synthesis of designable heteropolymers. As such, our method can guide the engineering of new types of self‐assembling modular polymers, that will open new possibilities for polymer‐based materials with unmatched versatility and control. Abstract : Designability phase diagram of a generalised heteropolymer decorated with directional interactions. The alphabet size represents the letters used in the design. The dots and the crosses are results of direct simulations, while the black line is the prediction from our operative definition of designability. The agreement between the two proves the remarkable prediction power of our methodology.